Digital literacy and competencies in library and information science education students in Nnamdi Azikiwe University Awka - Ngọzi Njideka Okechukwu; Chinemerem Chika Jacinta; Nnatu Agatha Ujunwa (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2025)
This study delves into the digital literacy and competencies of Library and Information Science (LIS) students at Nnamdi Azikiwe University, Awka. Employing a quantitative approach with a descriptive survey design, data were gathered from 68 participants via a structured questionnaire on Google Survey. The questionnaire, using a 4-point Likert scale, covered demographic details, digital literacy levels, perceived curriculum effectiveness, impacts of pedagogical methods, identified barriers, and suggested improvement strategies. Analysis through descriptive statistics and Analysis of Variance (ANOVA) provided understandings into the digital proficiency of LIS students, revealing notable gender differences. Results highlighted the expectations for LIS students to excel in digital libraries, archiving, system software, and communication. However, varying curriculum effectiveness was noted, influenced by accreditation standards and faculty expertise. Pedagogical methods such as hands-on learning and collaborative projects were found to enhance digital competencies, despite existing barriers like funding limitations and rigid curricula. The study advocates for curriculum enhancements, innovative pedagogy, and strategic interventions to bolster digital literacy in LIS programs.